The Chemistry of Frozen Vegetables - Steinka, Izabela; Barone, Caterina; Parisi, Salvatore; Micali, Marina; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This Brief presents a chemical perspective on frozen vegetables, also known as "ready-to-use" foods. It elucidates the chemical properties and modifications of vegetables from harvest and treatment to the end of their long shelf-life. Particular attention is given to the microbiological colonization of vegetables during the freezing treatments and to the chemical and physical modifications associated. The authors explore the undesired effects of this colonization through the lens of the antibiotic-resistant Staphylococci found in hermetically-package frozen vegetables. With this informative and instructive Brief, readers will understand the importance of the frozen storage technologies. .
Antibiotic-resistant Staphylococci Isolated from Hermetically-packaged Frozen Vegetables -- Technology and Chemical Features of Frozen Vegetables -- Instrumental Systems for the Control of Frozen Vegetables During Refrigeration -- Colorimetric Modifications in Frozen Vegetables.
Keywords: Food science; Food -- Microbiology; Nutrition .; Food Science; Food Microbiology; Nutrition